Peningkatan Hasil Belajar Matematika melalui Model Problem Based Learning dengan Pendekatan Saintifik pada Siswa Kelas VI SD Islam 34 Al Azhar Makassar - Diani Asbasari Jarsyah; Irfawandi Samad (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
This type of research uses Classroom Action Research using two cycles. Each cycle consists of 4 stages, namely 1) action planning, 2) action implementation, 3) observation, 4) reflection. The purpose of this research is to improve the Problem Based Learning model through a scientific approach. The location of the research was carried out at the Islamic Elementary School 34 Al Azhar Makassar, South Sulawesi Province, class VI with 26 students with 16 male students and 11 female students. In the first cycle the percentage level is 57.69 with a frequency value of 15 in the incomplete category, the percentage level is 42.31 with a frequency value of 11 in the complete category. In cycle II the percentage level is 11.53 with a frequency value of 3 in the incomplete category, the percentage level is 88.47 with a frequency value of 23 in the complete category. The results of the qualitative and quantitative data show that the mathematics learning outcomes of SD Islam 34 Al Azhar Makassar on the Problem Based Learning model through a scientific approach there is an increase in student learning outcomes.